Growth Performance of Striped Catfish (Pangasianodon hypopthalmus) Fed by Fermented Water Hyacinth - Santi Ramayani; Indra Suharman; Iesje Lukistyowati (Jurnal Perikanan dan Kelautan, 2022)
Fermented water hyacinth by Aspergillus niger can be used as alternative ingredient replacing soymeal for feed in striped catfish. The experimental designed consist of five treatment substitution of soymeal used fermented water hyacinth and three repliacate:  T0 (feed without FWH); T1 (25% FWH); P2 ( 50% FWH); P3 (75% FWH); and P4 (100% FWH. ). A total of 375 Striped catfish weight 4.21 ± 0.42 g were stocked with a density of 25 fish m-3 in fixed net cages. The study was conducted for 42 days. The results showed that the treatment given improved growth, feed convertion, and survival rate of striped catfish at dose FWH 50% It is recommended that substitution FWH 50% can used to replacing soymeal for feed striped catfish